Effect of Aflatoxin B1 in both Caco-2 and Caco-2/HT29-MTX models - Serrenho, I. (2022)
About effect of Aflatoxin B1 in both Caco-2 and Caco-2/HT29-MTX models within the scope of the intestinal absorption assessment and enabling formulations.